2017
DOI: 10.1371/journal.pone.0180986
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Outcome reporting bias is a problem in high impact factor neurology journals

Abstract: BackgroundSelective outcome reporting is a significant methodological concern. Comparisons between the outcomes reported in clinical trial registrations and those later published allow investigators to understand the extent of selection bias among trialists. We examined the possibility of selective outcome reporting in randomized controlled trials (RCTs) published in neurology journals.MethodsWe searched PubMed for randomized controlled trials from Jan 1, 2010 –Dec 31, 2015 published in the top 3 impact factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…For example, when a randomized controlled trial (RCT) contains an outcome deemed "not significant" and is selectively removed from a trial, the validity of the RCT may be questioned. Previous studies have already established outcome reporting bias as an issue within neurology, noting that only 40% of analyzed RCTs were preregistered and, therefore, prespecified their analysis [15]. This same study found outcome reporting inconsistencies that often favored statistically significant results [15].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, when a randomized controlled trial (RCT) contains an outcome deemed "not significant" and is selectively removed from a trial, the validity of the RCT may be questioned. Previous studies have already established outcome reporting bias as an issue within neurology, noting that only 40% of analyzed RCTs were preregistered and, therefore, prespecified their analysis [15]. This same study found outcome reporting inconsistencies that often favored statistically significant results [15].…”
Section: Discussionmentioning
confidence: 82%
“…In neurology, an audit of randomized clinical trials published in neurology journals found 180 outcome inconsistencies across 180 trials, with most inconsistencies favoring changes in accordance with statistically significant results. Additionally, only 55% of neurology trials were prospectively registered [15], providing indications that neurology researchers are not adhering to transparency and reproducibility practices early in research planning. Reproducible research and open science practices are widely endorsed by a large proportion of authors.…”
Section: Introductionmentioning
confidence: 99%
“…Howard et al . assessed 180 neurology clinical trials, finding 180 major discrepancies. Findings from Rankin et al .…”
Section: Discussionmentioning
confidence: 99%
“…compared outcomes listed in trial protocols with published reports . However, a large majority of studies have used the information included in clinical trial registries, such as ClinicalTrials.gov, to evaluate the discrepancies in outcomes between the trial registration and its publication . Use of the trial registration has two primary benefits for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Howard and colleagues found that industry‐funded neurology studies were more likely to have improperly registered their RCT in favour of statistically significant results (Howard et al. ), and Varner discussed extensively about potential bias in the field of ophthalmology (Varner ). When Alasbali et al.…”
Section: Discussionmentioning
confidence: 99%